2014
DOI: 10.1111/liv.12616
|View full text |Cite
|
Sign up to set email alerts
|

High post‐transplant virological response in hepatitis C virus infected patients treated with pretransplant protease inhibitor‐based triple therapy

Abstract: Overall SVR12 and pTVR12 rates are high among patients treated with PI-based triple therapy while awaiting LT, even in this difficult to treat population. However, caution is needed as early discontinuation and serious adverse events are common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
(67 reference statements)
0
7
0
Order By: Relevance
“…The addition of first-generation protease inhibitors (PIs), boceprevir and telaprevir, to PR is clearly associated with an increase in response rates in G1 infected patients [12][13][14][15][16], including some patients awaiting LT. Verna et al [17] reported the results of triple therapy in a small cohort of HCV-infected cirrhotic patients (n = 29) on the waiting list for LT (Child-Pugh A 62%, Child-Pugh B 38%). The median duration of treatment was 27 weeks.…”
Section: Interferon-based Regimensmentioning
confidence: 98%
“…The addition of first-generation protease inhibitors (PIs), boceprevir and telaprevir, to PR is clearly associated with an increase in response rates in G1 infected patients [12][13][14][15][16], including some patients awaiting LT. Verna et al [17] reported the results of triple therapy in a small cohort of HCV-infected cirrhotic patients (n = 29) on the waiting list for LT (Child-Pugh A 62%, Child-Pugh B 38%). The median duration of treatment was 27 weeks.…”
Section: Interferon-based Regimensmentioning
confidence: 98%
“…SVR12 rates increased approximately up to 60% -80% in HCV GT1-infected non-transplant patients (9,10) and up to 52% in liver transplant recipients since 2011, when a new family of medicines known as first generation direct-acting antivirals (DAAs) telaprevir and boceprevir were developed and introduced for use in combination with PegINF/RBV (8). PegINF, however, is associated with substantial side effects, which affect adherence to the interferon-based therapy (11).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…In clinical studies, the regimen consisting of OBV/PTV/r + DSV ± RBV was highly efficacious to treat HCV GT1a or GT1b infection, including patients with compensated cirrhosis, liver transplant or human immunodeficiency virus 1 (HIV-1) co-infection. The observed SVR12 rate ranged from 92% to 100% (8,(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The major concern with these regimens was the low tolerability rate. SAEs caused the discontinuation of therapy in 31% of patients (18). In the absence of alternative therapies, IFN-based therapy can only be an option for patients with a chance of better response rates, namely those with genotype 2-3 infection, IL28B CC polymorphism, CPT score <7, MELD<18, or HCC as indication for transplantation (19).…”
Section: Ifn-based Therapiesmentioning
confidence: 99%